2019
DOI: 10.1093/jrr/rrz065
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of zingerone derivate on ionizing radiation-induced intestinal injury

Abstract: Abstract Intestinal injury is the primary toxicity of radiotherapy for pelvic and abdominal tumors, and it is also one of the common acute complications of radiotherapy. At present, there are no effective drugs to prevent intestinal injury in the clinic. Zingerone is a natural product with radioprotective effects. In this study, a novel compound (thiazolidine hydrochloride, TZC01) was synthesized by structural modification of zingerone. The effects of TZC01 on pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Pretreatment of whole body radiation-exposure group with ginger showed significant improvement of oxidative stress. This coincided with the study of [24] reported that radiation induced reduction in intestinal tissue antioxidant enzyme levels such as superoxide dismutase, catalase, glutathione peroxidase, and glutathione which was reversed following administration of ginger essential oil.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Pretreatment of whole body radiation-exposure group with ginger showed significant improvement of oxidative stress. This coincided with the study of [24] reported that radiation induced reduction in intestinal tissue antioxidant enzyme levels such as superoxide dismutase, catalase, glutathione peroxidase, and glutathione which was reversed following administration of ginger essential oil.…”
Section: Discussionsupporting
confidence: 87%
“…High radiation doses cause death whereas sublethal doses may induce diverse diseases, such as cancer, cardiovas cular diseases and cataracts [22]. In addition, ionizing radiation may cause harm to normal tissue with many complications that affect biological and physiological systems so they should be protected [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…This paper concludes that pretreatment with TZC01 can significantly improve intestinal crypt apoptosis, increase the number of Lgr5+ ISCs, and even reduce intestinal cell apoptosis, thus protecting the intestinal barrier from IR damage. However, the mechanism of TZC01 is not explained in this paper ( 27 ).…”
Section: Intestinal Stem Cell Injurymentioning
confidence: 89%
“…Antiviral therapy, liver transplantation and artificial liver are common medical choices for the treatment of ACLF clinically, resulting in significantly reduced mortality, which, however, still exhibits an unsatisfied overall therapeutic effects 3 . It has been demonstrated that in the process of liver failure, the liver tissue is subjected to the triple lethal whammy of immune injury, hypoxic-ischemic injury and endotoxemia and the inflammatory response is the central link in the process of pathological progression 4 . Toll-like receptor 4 (TLR4) is an intracellular pattern recognition receptor that can activate the nuclear factors-κB (NF-κB) signaling pathway, which can induce an inflammatory cascade and participate in the inflammatory injury process of multiple diseases 5,6 .…”
Section: Introductionmentioning
confidence: 99%